Antiplasmodial potential and safety evaluation of the ethanolic stem bark extract of Distemonanthus benthamianus Baill. (Leguminosae) - Felix Ayisi; Caleb Nketia Mensah; Lawrence Sheringham Borquaye (Scientific African, 2021)
Plants are recognized as possible sources of anti-plasmodial therapeutic agents. As such, the usage and development of herbal preparations for treating malaria and other diseases has garnered a lot of interest. In this work, the antiplasmodial and potential toxic effects of Distemonanthus benthamianus in the treatment of suspected malaria was evaluated. The important roles of inflammation and oxidative imbalance in malaria infection also led to a study of the inflammation inhibitory and antioxidant properties of the plant extract. Standard techniques were used to carry out phytochemical evaluations. Antiplasmodial action was assessed in suppressive and curative in vivo antiplasmodial models whereas the edema model of inflammation in chicks was utilized in the anti-inflammatory investigations. Phosphomolybdenum and DPPH radical scavenging assays were employed in assessing the antioxidant action of the extract. Toxicity was evaluated in murine models. Phytochemical investigations of the plant extract indicated positive results for alkaloids, coumarins, flavonoids, glycosides, triterpenoids, tannins and saponins. Distemonanthus benthamianus stem back extract exhibited significant antiplasmodial activities with maximum chemosuppression rates of 77% and 56% in the curative and suppressive tests respectively, and considerable improvement in survival rate. A 55% inhibition in the anti-inflammatory evaluations indicated moderate activity in the reduction of inflammation. In the PM assay, a total antioxidant capacity of 18.75 gAAE/100 g was obtained while in the DPPH assay, the IC50 was 24.83 µg/mL. Clinical biochemistry of blood samples after 14 days of treatment with extract showed no significant differences between control and extract-treatment groups for liver and kidney biomarkers. The extract's approximate median lethal dose (LD50) was >2000 mg/kg. The findings of this study show that Distemonanthus benthamianus stem back extract possess very good antimalarial capabilities and is relatively safe at low concentrations.